2019
DOI: 10.1016/j.jarmac.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic benefits of systematic and random interleaving for second language grammar learning.

Abstract: Repeatedly switching between a series of to-be-learned topics, also called interleaved practice, can improve learning over traditional, one-topic-at-a-time blocked practice. We investigated whether interleaving's benefits for second language learning are facilitated by random schedules, wherein training trials follow unpredictable patterns, or by systematically alternating schedules, wherein trials are predictably sorted. Students learned to conjugate Spanish verbs in the preterite and imperfect tenses and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…5 One of the reviewers pointed out that the interleaving condition did not incorporate randomization (e.g., ABC-CBA-CAB, rather than ABC-ABC-ABC) even though randomization has been typically used in previous studies on interleaved practice. Unpredictability stemming from randomization may be an important variable in the effectiveness of interleaved training schedules (as argued by Pan, Lovelett, Phun, & Rickard, 2019). 6 The treatment-specific effect sizes (Cohen's ds) concerned the pretest-posttest changes (rather than training data) for which blocked and interleaved practice were compared, because the posttest in the current study was administered 1 day after the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 One of the reviewers pointed out that the interleaving condition did not incorporate randomization (e.g., ABC-CBA-CAB, rather than ABC-ABC-ABC) even though randomization has been typically used in previous studies on interleaved practice. Unpredictability stemming from randomization may be an important variable in the effectiveness of interleaved training schedules (as argued by Pan, Lovelett, Phun, & Rickard, 2019). 6 The treatment-specific effect sizes (Cohen's ds) concerned the pretest-posttest changes (rather than training data) for which blocked and interleaved practice were compared, because the posttest in the current study was administered 1 day after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence has suggested that the interleaving effect extends to L2 grammar learning (Nakata & Suzuki, 2019b; Pan, Tajran, Lovelett, Osuna, & Rickard, 2019; Suzuki & Sunada, 2019; Suzuki, Yokosawa, & Aline, 2020). The advantage of interleaved practice was found in the acquisition of the English tense–aspect–mood distinction (Nakata & Suzuki, 2019b) and Spanish past‐tense morphology (Pan, Lovelett, Phun, & Rickard, 2019), as well as in English subject/object relative clause constructions (Suzuki & Sunada, 2019; Suzuki et al., 2020). For instance, in Nakata and Suzuki's (2019b) study, EFL learners were introduced to five structures from the English tense–aspect–mood system: simple past, present perfect, first conditional, second conditional, and third conditional.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Such improvements were, in effect size terms, relatively large compared to other pedagogical techniques 42,43 (despite some variation across stages and across problems) and comparable to interleaving-induced improvements in such domains as middle school mathematics 31,33 and second language learning. 2,28 Further, learning benefits were observed (a) for the case of long-term memory for factual content, (b) for the correctness of answers, (c) after retention intervals of at least one to several weeks, and (d) on surprise criterial tests but not on subsequent high-stakes exams. From the perspective of the literature on interleaving and related techniques (e.g., variability during practice), 44 the present results bolster the conclusion that the benefits of alternating between topics or skills during learning extend beyond the ability to classify category exemplars; these benefits can also encompass certain problem-solving skills.…”
Section: Discussionmentioning
confidence: 97%
“…As one example, an instructor might choose to interleave a series of different homework problems that require factual knowledge and the execution of stepwise procedures. Initial efforts to address these questions have focused involved interleaving in such domains as mathematics, 21,26,27 second language instruction, 2,28,29 and other areas. 30 To date, the emerging literature on such uses of interleaving has yielded promising results and especially in the domain of middle-school mathematics.…”
Section: Prior Research On Educationally-relevant Uses Of Interleaved Practicementioning
confidence: 99%